(untitled) (Altre Modernità, 2023)
The contribution offers a transversal reading of two travelogues by English women who travelled through the Abruzzi at the beginning of the 20th century: In the Abruzzi by Anne McDonell (1908) and Through the Apennines and the Lands of the Abruzzi: Landscape and Peasant Life by Estella Canziani (1928). Starting from an overview of the critical literature on women’s odeporic writing and its intertwining with the methodological frameworks that have investigated the imaginary landscape of Southern Italy, margin of the margin and contact zone between Europe and Africa, the analysis will focus on the differences in the structuring of the narrative voice and of the positionality of the gaze in these two accounts, in order to defuse the risk of flattening these subjectivities into a stereotype that does not give credit to the stratifications that these two writers display in their respective approaches to the Abruzzi territory. The counterpoint between rhetorical elements such as political commentary and irony for MacDonell and ethnographic and fable-like language for Canziani allows the reader to confront the complexities of the territories recounted and the communities that inhabit them; the intersection of these two positionalities contributes to a decidedly nuanced representation that questions easy binarisms such as civilised/primitive or tradition/modernity.